The Potential of 233U/236U as a Water Mass Tracer in the Arctic Ocean - Chamizo, Elena; Christl, Marcus; id_orcid:0 000-0002-3131-6652; López-Lora, Mercedes; Casacuberta, Núria; id_orcid:0 000-0001-7316-1655; Wefing, Anne-Marie; id_orcid:0 000-0001-6855-6062; Kenna, Timothy C. (American Geophysical Union, 2022)
This study explores for the first time the possibilities that the 233U/236U atom ratio offers to distinguish waters of Atlantic or Pacific origin in the Arctic Ocean. Atlantic waters entering the Arctic Ocean often carry an isotopic signature dominantly originating from European reprocessing facilities with some smaller contribution from global fallout nuclides, whereas northern Pacific waters are labeled with nuclides released during the atmospheric nuclear testing period only. In the Arctic Ocean, 233U originates from global fallout while 236U carries both, a global fallout and a prominent nuclear reprocessing signal. Thus, the 233U/236U ratio provides a tool to identify water masses with distinct U sources. In this work, 233U and 236U were analyzed in samples from the GN01 GEOTRACES expedition to the western Arctic Ocean in 2015. The study of depth profiles and surface seawater samples shows that: (a) Pacific and Atlantic waters show enhanced signals of both radionuclides, which can be unraveled based on their 233U/236U signature; and (b) Deep and Bottom Waters show extremely low 233U and 236U concentrations close to or below analytical detection limits with isotopic ratios distinct from known anthropogenic U sources. The comparably high 233U/236U ratios are interpreted as a relative increase of naturally occurring 233U and 236U and thus for gradually reaching natural 233U/236U levels in the deep Arctic Ocean. Our results set the basis for future studies using the 233U/236U ratio to distinguish anthropogenic and pre-anthropogenic U in the Arctic Ocean and beyond. ISSN:0148-0227 ISSN:2169-9275